The impact of Pasifikas in Medicine on Pacific Islander medical student experiences - Devon Hori Harvey; Micah Ngatuvai; Siale Vaitohi; Paige E. Faasuamalie; Maegan Tupinio; Lisa H. Smith (PLoS ONE, 2025)
Background Pacific Islanders experience significant health disparities. One contributing aspect to these disparities is the lack of racial concordance as Pacific Islanders are underrepresented in the U.S. physician work force. Several factors contribute to this underrepresentation including lack of support systems for Pacific Islander premed and medical students. Pasifikas in Medicine (PiM) is a recently established national student organization founded to provide support for Pacific Islander premed students, medical students, residents, fellows and attending physicians. This study seeks to understand the impact of PiM on medical student experiences. Methods An anonymous survey was distributed to the PiM listserv and to Diversity, Equity and Inclusion offices of allopathic and osteopathic medical schools across the U.S. The survey included seven questions for demographic data, ten 5-point ordinal questions to evaluate the impact of PiM on medical student experiences, and three free text questions. Results A total of 34 individuals participated in the study with 21 individuals completing the evaluative portion of the survey. Of 28 who responded, 27 (96.4%) were the first in their family to attend medical school, and 25 (89.2%), planned to serve Pacific Islander patient populations in their medical career. For the 10 evaluative questions, 7 scored ≥ 4.0 of of 5.0. Identifying Mentors, Faculty Networking, and Research Opportunities scored less well. Qualitative data was favorable of PiM and demonstrated significant camaraderie, community, and connection to other Pacific Islander physicians and medical students. Conclusion Pasifikas in Medicine fills an unmet need by creating a space dedicated to addressing the challenges unique to Pacific Islander students, separate from other minority groups. Improvements to PiM should begin with creating more mentorship opportunities, faculty networking and research opportunities. Additionally, increasing PiM presence nationally and locally within medical schools could further strengthen Pacific Islander medical student experience.